2018
DOI: 10.1103/physrevb.97.235153
|View full text |Cite
|
Sign up to set email alerts
|

Surface- and pressure-induced bulk Kondo breakdown in SmB6

Abstract: Motivated by the prediction of surface Kondo breakdown in topological Kondo insulators, we investigated the valence and magnetism of SmB 6 with x-ray absorption and magnetic circular dichroism at the Sm M 4,5 and L 2 edges with surface and bulk sensitivity, respectively. A higher Sm valence state at the surface and in the bulk under pressure indicates the surface-and pressure-induced bulk Kondo breakdown. We confirmed the different magnetization origin from the surface (f electron) to the bulk (d electron) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 50 publications
(74 reference statements)
1
6
0
Order By: Relevance
“…Inelastic neutron scattering observes both J 4f = 0 → 1 and J 4f = 5/2 → 7/2 spin-flip excitations [19], with the latter excitation only attributable to the magnetic (metallic) Sm 3+ state, and µSR measurements find magnetic fluctuations that are homogeneous, dynamic and spatially coherent up to ξ 100 nm [16,17], rather than existing as inhomogeneous spatially static regions. Remarkably, application of relatively modest hydrostatic pressure (4-10 GPa) is sufficient to completely destroy the Kondo gap in SmB 6 [40][41][42][43][44]. XAS has tracked the Sm 2+ and Sm 3+ populations as a function of pressure through the metallic transition and found that the Sm 3+ state dominates above 10 GPa [42,43].…”
mentioning
confidence: 99%
“…Inelastic neutron scattering observes both J 4f = 0 → 1 and J 4f = 5/2 → 7/2 spin-flip excitations [19], with the latter excitation only attributable to the magnetic (metallic) Sm 3+ state, and µSR measurements find magnetic fluctuations that are homogeneous, dynamic and spatially coherent up to ξ 100 nm [16,17], rather than existing as inhomogeneous spatially static regions. Remarkably, application of relatively modest hydrostatic pressure (4-10 GPa) is sufficient to completely destroy the Kondo gap in SmB 6 [40][41][42][43][44]. XAS has tracked the Sm 2+ and Sm 3+ populations as a function of pressure through the metallic transition and found that the Sm 3+ state dominates above 10 GPa [42,43].…”
mentioning
confidence: 99%
“…We note that XMCD of another floating-zone sample with a small magnetic impurity concentration (inferred by magnetization) was recently reported. [47] The total moment of Sm 3+ was reported as aligned with field at the surface (TEY), with a very small contribution antialigned within the bulk(TFY). In contrast, we observe an anti-aligned moment for Sm 3+ at the surface and within the bulk occurring at similar magnitudes.…”
mentioning
confidence: 99%
“…Phelan et al confirm the presence of Sm 2+ and Sm 3+ in the bulk of floating-zone 1.5 Bulk properties 35 crystals; however, the polished surface is shown to contain mostly Sm 3+ with a net magnetic moment of 0.09 µ B at T = 10 K. The authors argue that the discrepancy between the valence at the surface and in the bulk could generate band bending at the interface. Though Chen et al also report a higher Sm valence at the surface of powdered floating-zone SmB 6 , the extracted value of ν = 2.7 is below the trivalent state [155]. Employing the same techniques on vacuum-cleaved samples reveal that both divalent and trivalent Sm are present on the surface of SmB 6 , indicating that polishing has a significant effect on the surface valence [158].…”
Section: X-ray Neutron and Mössbauer Spectroscopiesmentioning
confidence: 91%
“…This critical pressure is dependent on the hydrostaticity of the pressure media and may be as low as ∼ 4 GPa in quasi-hydrostatic environments [149][150][151]. X-ray spectroscopy measurements report the increase in Sm valence under pressure towards the trivalent state as the systems goes towards the antiferromagnetic metallic ground state [152][153][154][155][156]. A discrepancy, however, is observed in the quantitative analysis by different groups.…”
Section: X-ray Neutron and Mössbauer Spectroscopiesmentioning
confidence: 99%
See 1 more Smart Citation